KORELASI ANTARA MOTIVASI DAN AKTIVITAS BELAJAR DENGAN HASIL BELAJAR TEMATIK KELAS IV SDS - Winawati Winawati; Tahmid Sabri; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to describe the correlation between motivation and study activity withlearning outcomes in the thematic learning of class IV Elementary School PrivateSekecamatan Pontianak Selatan. The research method used is descriptive in the form ofcorrelational study research. The population in this study was the students of ElementarySchool Cluster Sekecamatan Pontianak Selatan numbering 655 students. The samples inthe study were 78 students who were determined by sample random sampling technique,namely the IVE class Mujahidin Elementary School Pontianak Selatan totaling 38students, IV class LKIA Elementary School Pontianak Selatan totaling 14 students andthe IV class Budi Baik Elementary School Pontianak Selatan totaling 26 students. Theresults of the study showed an average motivation learning of 80,44%, study activity of78,9%, and learning outcomes of 80,63. Statistical calculations using the product momentcorrelation formula namely learning motivation with learning outcomes obtained rhitung of0.269 and study activity with learning outcomes obtained rhitung of 0.42. For motivationand study activity with learning outcomes using the multiple correlation formula obtainedby 0.475 included in the category of moderate relations with Fhitung at 10.93 and Ftabel α =5% at 3.12 which means Fhitung (10.93)> Ftabel (3,12), then Ha is accepted. So, it can beconcluded that there is a relationship between motivation and study activity with learningoutcomes in the thematic learning of class IV Elementary School Private SekecamatanPontianak Selatan.Keywords: Correlation, Learning Motivation, Study Activity, Learning Outcomes, andThematic Learning